Sulphur emissions to the stratosphere from explosive volcanic eruptions - Pyle, D; Beattie, P; Bluth, G (Bulletin of Volcanology, 2016)
Two methods were used to quantify the flux of volcanic sulphur (as the equivalent mass of SO2) to the stratosphere over different timescales during the Holocene. A combination of satellite-based measurements of sulphur yields from recent explosive volcanic eruptions with an appropriate rate of explosive volcanism for the past 200 years constrains the medium-term (≃102 years) flux of volcanic sulphur to the stratosphere to be ≃ 1 Mt a-1, with lower and upper bounds of 0.3 and 3 Mt a-1. The short-term ( ≃ 10- to 20-year) flux due to small magnitude (1010-1012kg) eruptions is of the order of 0.4 Mt a-1. At any time the instantaneous levels of sulphur in the stratosphere are dominated by the most recent (0-3 years) volcanic events. The flux calculations do not attempt to address this very short timescale variability. Although there are significant errors associated with the raw sulphur emission data on which this analysis is based, the approach presented is general and may be readily modified as the quantity and quality of the data improve. Data from a Greenland ice core support these conclusions. Integration of the sulphate signals from presumed volcanic sources recorded in the GISP2 core provides a minimum estimate of the 103-year volcanic SO2 flux to the stratosphere of 0.5-1 Mt a-1 over the past 9000 years. The short-term flux calculations do not account for the impact of rare, large events. The ice-core record does not fully account for the contribution from small, frequent events.